Extracellular vesicles: their challenges and benefits as potential biomarkers for musculoskeletal disorders - Soo-Eun Sung; Min-Soo Seo; Wook-Tae Park; Young-Ju Lim; Sangbum Park; Gun Woo Lee (Journal of International Medical Research)
Early diagnosis and timely management are critical for determining disease outcomes and prognoses. To date, certain methods for developing disease-specific biomarkers have been reported; however, strategies for musculoskeletal disease-specific biomarker development have rarely been studied. Recent studies have highlighted the potential application of extracellular vesicles (EVs) as disease-specific biomarkers. EVs encapsulate proteins, lipids, messenger RNAs, and microRNAs derived from their cellular origin; these constituents remain stable within the EVs and can traverse the blood–brain barrier. Because of these distinctive characteristics, EVs have been actively investigated as diagnostic tools for various conditions, including cancer, inflammatory diseases, and musculoskeletal disorders. Although EVs have many advantages for biomarker development, they have not yet been fully researched in the context of musculoskeletal pathologies. The current review aimed to highlight the potential of EVs in the development of disease-specific biomarkers, summarize the processes of EV biomarkers, and discuss current limitations and future perspectives of EVs as biomarkers.